2021
DOI: 10.1371/journal.pone.0244430
|View full text |Cite
|
Sign up to set email alerts
|

PFP-WGAN: Protein function prediction by discovering Gene Ontology term correlations with generative adversarial networks

Abstract: Understanding the functionality of proteins has emerged as a critical problem in recent years due to significant roles of these macro-molecules in biological mechanisms. However, in-laboratory techniques for protein function prediction are not as efficient as methods developed and processed for protein sequencing. While more than 70 million protein sequences are available today, only the functionality of around one percent of them are known. These facts have encouraged researchers to develop computational meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Specifically, a GO annotation is an association between a specific gene product and a GO concept. GO was well established and has often been used to evaluate the quality of newly constructed or reconstructed protein-protein interaction networks (Xu et al, 2018;Seyyedsalehi et al, 2021). We focused on BP ontology enrichment analysis since we are interested in what biological processes are involved in COPD.…”
Section: Gene Ontology Enrichment Analysis On Hub Proteins In Copd Associated Networkmentioning
confidence: 99%
“…Specifically, a GO annotation is an association between a specific gene product and a GO concept. GO was well established and has often been used to evaluate the quality of newly constructed or reconstructed protein-protein interaction networks (Xu et al, 2018;Seyyedsalehi et al, 2021). We focused on BP ontology enrichment analysis since we are interested in what biological processes are involved in COPD.…”
Section: Gene Ontology Enrichment Analysis On Hub Proteins In Copd Associated Networkmentioning
confidence: 99%
“…The goal of the Critical Assessment of Protein Function Annotation (CAFA) programme is to evaluate protein function prediction methods on a large scale. The results of the first two CAFA challenges showed that protein function prediction is still a difficult area to study [11], [12]. Artificial neural networks (ANNs) and other machine learning methods have been used to predict protein function [13].…”
Section: Functional Classification Schemesmentioning
confidence: 99%
“…Over the past decade, several GO term-based protein activity prediction methods has been proposed to automate protein sequencing using machine learning and statistical analysis methods [12], [13], [14]. Considering the forecast performance of the current methods, it can be said that there is still room for significant improvement in this area.…”
Section: )mentioning
confidence: 99%